O (nie)potrzebności humanistyki; On the (un)necessity of the humanities - Małgorzata Popiołek-Roßkamp (Quart: Quarterly of Art History Institute at the University of Wrocław, 2022)
– The purpose of this essay is to examine the situation of the contemporary humanities and the challenges they face, and to reflect on their future. For the last few decades, the humanities have been trying to emphasize their value by constructing more and more new “research tools”, which were supposed to allow them to compete with the sciences. According to the author of the text, instead of making their functioning similar to the way other sciences operate, the humanities should focus, on the one hand, on popularising their own achievements and, on the other, on promoting the universality of their tasks in society. The primary function of the humanities is to educate a society capable of independent thought, questioning and doubt. The humanities also allow people to reflect more broadly on their own place in the world. For this reason, one of the main threats to this field is the attempt to apply to it the principles of the free market. Humanities reduced to the role of a product will lose their elemental value.
Keywords: 300